2020
DOI: 10.1029/2020jc016465
|View full text |Cite
|
Sign up to set email alerts
|

Wave Generation Across a Continuum of Landslide Conditions From the Collapse of Partially Submerged to Fully Submerged Granular Columns

Abstract: Landslides commonly occur on earth's surface, in a wide range from subaerial landscapes to submarine oceanic regions. These events can trigger the generation of hazardous tsunamis that can have major consequences such as overtopping of dams and reservoirs, and coastal flooding and erosion. Globally, tsunamis have caused more than 250,000 fatalities over the past 30 years, triggered by landslides, earthquakes, and other sources combined (Gusiakov et al., 2019), and for this reason they are one of the primary na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 45 publications
11
34
0
Order By: Relevance
“…The generation of tsunami waves by landslides may be triggered by volcanic or seismic events not only in the ocean, but also in lakes or rivers (Kremer, Simpson & Girardclos 2012;Couston, Mei & Alam 2015), due to the collapse or avalanche of either soil, rocks, or even ice and snow (Zitti et al 2016). The experimental and numerical studies of Clous & Abadie (2019) and Cabrera et al (2020) have recently shown that subaerial landslides trigger much larger waves than submarine landslides for a given amount of destabilized materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of tsunami waves by landslides may be triggered by volcanic or seismic events not only in the ocean, but also in lakes or rivers (Kremer, Simpson & Girardclos 2012;Couston, Mei & Alam 2015), due to the collapse or avalanche of either soil, rocks, or even ice and snow (Zitti et al 2016). The experimental and numerical studies of Clous & Abadie (2019) and Cabrera et al (2020) have recently shown that subaerial landslides trigger much larger waves than submarine landslides for a given amount of destabilized materials.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental and numerical studies of Clous & Abadie (2019) and Cabrera et al. (2020) have recently shown that subaerial landslides trigger much larger waves than submarine landslides for a given amount of destabilized materials.…”
Section: Introductionmentioning
confidence: 99%
“…In these events, the sudden release of a collection of grains is followed by a granular flow driven by gravity, with a combination of intensive and continuous interactions between the grains, the topography, and the ambient fluid (Delannay et al., 2017). A common characteristic among these events is their large mobility, exceeding the prediction of simple frictional models (Corominas, 1996; Davies & McSaveney, 1999; Heim, 1932; Hsu, 1975; Legros, 2002) and emphasizing their hazardous perception when interacting with infrastructure, communities, or other land masses (Cabrera et al., 2020; Froude & Petley, 2018). The proposed mechanisms behind this large mobility are varied, including excessive reductions of the flow basal friction, for example, the formation of an air cushion (Shreve, 1968); size segregation (Iverson et al., 2010; Roche et al., 2011); a series of interactions that weaken the collective shear resistance, for example, fluid, air, or fines fluidization (Collins & Melosh, 2003; Kent, 1966; Hsu, 1975); self‐lubrication (De Blasio & Elverhøi, 2008; Goren & Aharonov, 2007); dynamic rock‐fragmentation (Davies & McSaveney, 2009); and volume‐induced frictional weakening (Borykov et al., 2019; Lucas et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The granular column experiments are performed in the planar setup developed by Pinzon & Cabrera (see Fig. 1), and employed in the study of submerged column collapses [15,16] and landslide generated waves [17]. In this setup, the model PMMA side windows are separated by a thin gap, confining the granular material to a nearly two-dimensional configuration.…”
Section: Methodsmentioning
confidence: 99%